What Causes Extreme Precipitation in the Southern Philippines During El Niño Winters? - Zhang, Wen-Jun; Wu, Renguang; Dai, Panxi; Gu, Qinlu (Journal of climate, 2025)
As an archipelagic nation, the Philippines is highly susceptible to the adverse impacts of weather-related hazards, notably extreme precipitation events. Despite the typical dry conditions associated with the warm phase of El Niño–Southern Oscillation (ENSO), this study unravels that extreme precipitation can occur in the southern Philippines during boreal winters of El Niño events. The extreme precipitation is caused by two distinct wind systems. One is the northwestward-moving tropical cyclones or tropical depressions (TCs/TDs), and the other is the southward-moving northeasterly cold surges (CSs). Additionally, the northward extension of the eastward-propagating Madden–Julian oscillation (MJO) wet phase contributes to extreme precipitation in the southern Philippines. The northwestward-moving TCs/TDs and the southward-moving northeasterly CSs reach the southern Philippines under the guidance of the MJO wet phase. A comparative analysis between extreme and weak precipitation days reveals that westward-shifted positive sea surface temperature (SST) anomalies in the equatorial Pacific favor the generation of TCs/TDs in the western part of the tropical western North Pacific and CSs over East Asia. This study suggests a critical role of multiscale influences in the occurrence of extreme precipitation in the southern Philippines during El Niño winters.